Fields and trade economic cooperation between Iran and Tajikistan after independence from the Soviet Union to the present (International Journal of Scientific Research and Management (IJSRM), 2022)
Trade between countries today plays an important role in international relations and is one of the indicators for measuring the level of development of countries. Some countries have even re-exported in order to have a good position in the world rankings. Iran’s economic relations with Tajikistan have had ups and downs, and over the years many Iranian companies have been involved in development projects - dams - roads - tunnels ....Tajikistan. This article examines trade relations between the two countries after Tajikistan gained independence